Annual Variation of Global Air Pollution: Initial Aerosol Effect or Climate Interaction? - Feng, Huihui; Ding, Ying; Zou, Bin; Zhao, Chuanfeng (Frontiers in Environmental Science, 2021)
The aerosol at the previous time (initial aerosol) and climate conditions control the next step annual variation of global air pollution through the complex aerosol-climate interaction. However, the individual influences remain unclear, leaving a great gap for understanding the mechanism of air pollution evolution and supporting the environment management. We estimate the annual variation using statistical methods and satellite observations at global scale from 2001 to 2016 . Results show that significant variation of annual aerosol occurs over 13.6% of land areas, in which a perturbation of aerosol may cause 0.58±0.45 times change in the next phase. Initial aerosol and climate influences contribute 48.4% and 51.6% of the total variation, respectively. Specifically, the influences of precipitation, air temperature and surface temperature represent 0.1%, 18.3% and 33.2% of the total variation. Physically, the observed variation is strongly correlated with fine mode aerosols, radiative scattering and warm/hot summers in temperate and cold zones. The environmental management therefore should implement cause-oriented strategies for emission control or climatic adaption.